Lagen som ett retoriskt objekt - En analys av gamla och nya konsumentköplagen - Rosén,Lukas (2023)
The thesis aims to provide a theoretical perspective on the language used in the Swedish law. Through a rhetorical argumentation analysis, grounded in Chaïm Perelman’s theory of perceived audiences and Lloyd Bitzer’s theory of the rhetorical situation, the consumer sales act is investigated in its capacity as a carrier of meaning between a speaker and an audience. The old and the new consumer sales act is qualitatively compared. The choices the legislator made in the construction of these two laws are juxtaposed with the construed discourse about legal language in codification, the historical debate, and the broader juridical tradition. Some of the conclusions are that there is a long-standing intention to try to make the legal language more easily approachable for the public – especially in the consumer sales act – but that this intention has been sidelined when constructing the new consumer sales act. The reason for this seems to be a change in the rhetorical situation, followed by the increased scope of the legislation. Perelman’s fragmentation of the audience is used to define and place different audience groups in a hierarchy of how much the legislator prioritizes the needs of these groups in the legal language. At the top we find the jurists, at the bottom we find the consumers. There is a discrepancy between the construed discourse and reality when this rhetorical theoretical framework is used. It points to an underlying problem in how law is written. A problem the jurists have been made to solve, but one that is not compatible with a legal language that is supposedly easily approachable for the public.
Keywords: allmän rättslära; rättshistoria; rättsvetenskap; Perelman; Bitzer; konsumentköplagen; rättslingvistik; rättsretorik